MODERN VIEWS ON THE SURGICAL TREATMENT OF PATIENTS WITH THE CONSEQUENCES OF BURNS OF THE FINGERS OF THE HAND IN CHILDREN (literary review) (World Bulletin of Public Health, 2024)
Thermal lesions pose a serious medical and economic problem. In industrialized countries, 300-380 cases of burns of various localization per 100,000 people are registered daily. Almost every minute, somewhere in the world, a person becomes a victim of burns with all the ensuing medical and social consequences.
Keywords: surgical treatment; burn; brush